Cuidados paliativos: relação dialógica entre enfermeiros e pacientes em fase terminal - Alves, Adriana Marques Pereira de Melo (2018)
Introduction: Palliative care is care directed to a person whose illness no longer responds to curative treatment. It is a differentiated care approach that aims to improve the quality of life of patients and their families when facing the process of a chronic, progressive and incurable disease. For this, the participation of the nurse as a member of the palliative team is essential for the promotion of a humanized care for the terminally ill patient, with an emphasis on the dialogical relationship. Objectives: to analyze the dialogical relationship between nurses and patients in the terminal phase under palliative care, in the light of the Humanistic Nursing Theory and to identify the communication strategies used by nurses to promote palliative care to terminally ill patients. Methodology: This is a field research of a qualitative nature that was developed in medical clinic units of a public hospital in the city of João Pessoa-PB-Brazil. Twenty assisting nurses participated in the study. For the data collection, the interview technique was used based on a script with questions pertinent to the objectives proposed for the research. Data collection occurred in July, August and September 2017, after approval of the research protocol by a Research Ethics Committee. The empirical material was analyzed in the light of the Humanistic Theory of Nursing. Results: From the data collected, two articles emerged: (1) Communication strategies adopted by nurses to the terminal patient under palliative care: a study based on the Humanistic Nursing Theory. (2) Dialogical relationship between nurses and the terminal patient under palliative care. From the first manuscript from the statements of the nurses involved it was observed that effective communication, whether verbal or non-verbal, is based on the know-how, on the perception and empathy that is established in the relationship of the caring being and the being that is cared for, well as respecting the dignity of the terminal patient under palliative care. These testimonies show that the professionals guide their assistance to these patients, based on the philosophy of Humanistic Nursing Theory. In the second article, considering that communication reveals itself as a fundamental nucleus in the nurse-patient relationship, it is understood by the study participants as one of the most important and essential instruments in palliative care. They recognize the value of non-verbal communication expressed through touch, gestures of affection, smile and bodily attitudes that represent measures of comfort and well-being and help in improving the relief of suffering by promoting the quality of life to the patient in the process of finitude. Conclusion: Thus, both articles emphasize the importance of communication to promote humanized care and constitute an effective and indispensable component in nursing care to the terminal patient under palliative care. Thus, this research gives a new look not only in the field of patient care under palliative care, but also in the field of teaching and research in Nursing, so that future studies can be carried out with the purpose of knowledge about the subject.